Length-weight relationship and relative condition factor of the ribbon fish, Lepturacanthus savala (Cuvier, 1829) from the Bay of Bengal, Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Length-weight relationship of 1119 specimens of Lepturacanthus savala (Cuvier 1829) from the Bay of Bengal, Bangladesh, was found to be curvilinear (W= 0.0003612 TL3.18) and linear (LogW= -3.44+3.18 LogTL) for both the sexes combined in arithmetic and logarithmic scales, respectively. The values of regression co-efficient (b) ranged from 3.002 to 3.337 (? ± 0.167) at 95% confidence limit. The regression 'b' value (3.18) followed the cube law and did not significantly (P>0.05) differ from the cube. The growth of the fish was found to be isometric. Relative condition factor (Kn) was also within the ideal range (0.9695 to 1.1155, mean 1.001± 0.033). Seasonal or in different length groups no dramatic changes in relative condition factor were observed. Length frequency distribution was found to be normal with maximum number of fish in mid length groups and minimum in the lowest and highest length groups. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13412 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):119-126, 2008